Integrated Coastal Vulnerability Index (ICVI) Assessment of Protaras Coast in Cyprus: Balancing Tourism and Coastal Risks - Theocharidis, Christos; Prodromou, Maria; Doukanari, Marina; Kalogirou, Eleftheria; Eliades, Marinos; Kontoes, Charalampos; Hadjimitsis, Diofantos G.; Neocleous, Kyriacos (My University, 2025)
Coastal areas are highly dynamic environments, vulnerable to natural processes and human interventions. This study presents the first application of the Integrated Coastal Vulnerability Index (ICVI) in Cyprus, focusing on two major tourism-dependent beaches, Fig Tree Bay and Vrysi Beach, located along the Protaras coastline. Despite their economic significance, these coastal areas face increasing vulnerability due to intensive tourism-driven modifications and natural coastal dynamics, necessitating a structured assessment framework. This research addresses this gap by integrating the ICVI with geographical information system (GIS) and analytic hierarchy process (AHP) methodologies to evaluate the coastal risks in this tourism-dependent environment, providing a replicable approach for similar Mediterranean coastal settings. Ten key parameters were analysed, including coastal slope, rate of coastline erosion, geomorphology, elevation, tidal range, wave height, relative sea level rise, land cover, population density, and road network. The results revealed spatial variations in vulnerability, with 16% of the coastline classified as having very high vulnerability and another 16% as having high vulnerability. Fig Tree Bay, which is part of this coastline, emerged as a critical hotspot due to its geomorphological instability, low elevation, and intensive human interventions, including seasonal beach modifications and infrastructure development. This study underscores the need for sustainable coastal management practices, including dune preservation, controlled development, and the integration of the ICVI into planning frameworks to balance economic growth and environmental conservation.
Keywords: Integrated Coastal Vulnerability Index (ICVI); Coastal Vulnerability Index (CVI); analytic hierarchy process (AHP); coastal erosion; eographic information system (GIS); remote sensing; coastal dynamics; tourism impact; Cyprus